Srikrsnavijayah Nalodayah - Menon, K. P. A. (Delhi, 1999)
This book is emphasized on Classical Sanskrit literature of Kerala. About the authership of Nalodaya there have been some controversies but its Kerala origin has now been widely accepted.
Keywords: Sanskrit literature-Translation into english